2014
DOI: 10.1371/journal.pone.0110633
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Response of Corophium volutator to Shorebird Predation in the Upper Bay of Fundy, Canada

Abstract: Predator avoidance is an important component of predator-prey relationships and can affect prey availability for foraging animals. Each summer, the burrow-dwelling amphipod Corophium volutator is heavily preyed upon by Semipalmated Sandpipers (Calidris pusilla) on mudflats in the upper Bay of Fundy, Canada. We conducted three complementary studies to determine if adult C. volutator exhibit predator avoidance behavior in the presence of sandpipers. In a field experiment, we monitored vertical distribution of C.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 86 publications
0
12
0
Order By: Relevance
“…Furthermore, Wrede et al (2018) suggested including a temperature correction factor (Q 10 ) in the calculations to account for the expected metabolic response of macrofauna to increasing water temperatures (Brey, 2010). This temperature effect on benthic activity has indeed been noticed in similar works (Magni and Montani, 2006;Rao et al, 2014), but in our study and others the highest temperatures were not clearly associated with the highest functional process rates (Schlüter et al, 2000;Braeckman et al, 2010;Queirios et al, 2015). The reasons for this ranged from a noncoincidence of the annual food pulse and the temperature peak to the presence of confounding factors in the analysis such as faunal abundances and behavior (Forster et al, 2003).…”
Section: The Bioirrigation Potentialmentioning
confidence: 55%
See 1 more Smart Citation
“…Furthermore, Wrede et al (2018) suggested including a temperature correction factor (Q 10 ) in the calculations to account for the expected metabolic response of macrofauna to increasing water temperatures (Brey, 2010). This temperature effect on benthic activity has indeed been noticed in similar works (Magni and Montani, 2006;Rao et al, 2014), but in our study and others the highest temperatures were not clearly associated with the highest functional process rates (Schlüter et al, 2000;Braeckman et al, 2010;Queirios et al, 2015). The reasons for this ranged from a noncoincidence of the annual food pulse and the temperature peak to the presence of confounding factors in the analysis such as faunal abundances and behavior (Forster et al, 2003).…”
Section: The Bioirrigation Potentialmentioning
confidence: 55%
“…Intertidal areas also experience stronger variations in physical stressors such as waves, temperature, light, salinity and precipitation than subtidal areas do (Herman et al, 2001) and are more subject to biological stressors such as predation by birds (Fleischer, 1983;Granadeiro et al, 2006;Ponsero et al, 2016). Burrowing more deeply or simply residing in deeper sediment layers for a longer time are valid strategies for species in the intertidal areas to combat these pressures (Koo et al, 2007;MacDonald et al, 2014).…”
Section: Spatiotemporal Variability In Bioirrigationmentioning
confidence: 99%
“…Intertidal areas experience stronger variations in physical stressors such as waves, temperature, light, salinity and precipitation than subtidal areas (Herman et al, 2001), and to biological stressors such as predation by birds (Fleischer, 1983;Granadeiro et al, 2006;Ponsero et al, 2016). Burrowing deeper, or simply residing in deeper sediment layers for a longer time, are valid strategies for species in the intertidal to combat these pressures (Koo et al, 2007;MacDonald et al, 2014).…”
Section: Spatio-temporal Variability In Bio-irrigationmentioning
confidence: 99%
“…Interference through prey depression was detected in redshank pecking for amphipods, but not in redshank and bar-tailed godwit (Limosa lapponica (L., 1758)) probing for annelids (Goss-Custard 1976;Selman and Goss-Custard 1988;Yates et al 2000;Minderman et al 2006). This is because amphipods, C. volutator and Orchestia spp., which are commonly preyed upon by shorebirds, in the presence of predators reposition themselves from mud surface deeper into their burrows, thus becoming temporarily less available to birds that are feeding by sight (Goss-Custard 1976;Minderman et al 2006;MacDonald et al 2014). The average response distance of C. volutator, at which they retreat deeper into the sediment in the presence of redshank, is 0.6 m (range 0.1 to 1 m) (Stillman et al 2000).…”
Section: R a F Tmentioning
confidence: 99%